2011
DOI: 10.1117/1.3541780
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of very small line patterns in critical dimension scanning electron microscopy using model-based library matching technique

Abstract: Our purpose is to reduce the critical dimension (CD) bias for very small patterns with line widths of <15 nm. The model-based library (MBL) method, which estimates the dimensions and shape of a target pattern by comparing a measured scanning electron microscopy image waveform with a library of simulated waveforms, was modified in two ways. The first modification was the introduction of line-width variation into the library to overcome problems caused by significant changes in waveform due to changes in both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There have been several studies on the analysis of SEM images using such a simulator. [14][15][16][17][18][19][20][21][22][23] Shishido et al reported that at an acceleration voltage of 800 V, Monte-Carlo simulation SEM images matched experimental SEM images for patterns with line widths of 8 to 32 nm. 19) As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies on the analysis of SEM images using such a simulator. [14][15][16][17][18][19][20][21][22][23] Shishido et al reported that at an acceleration voltage of 800 V, Monte-Carlo simulation SEM images matched experimental SEM images for patterns with line widths of 8 to 32 nm. 19) As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23] Shishido et al reported that at an acceleration voltage of 800 V, Monte-Carlo simulation SEM images matched experimental SEM images for patterns with line widths of 8 to 32 nm. 19) As shown in Fig. 1(a), when the pattern size is larger than the PE scattering range, the SEM line profile has peaks at both ends of the line pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these being essential difficulties encountered in SEM photometric stereo, an accurate estimation of all such brightness fluctuations is not realistic, given the high modeling and processing costs for various pattern variations (e.g. Monte Carlo simulation and the model-based library (MBL) method [17,18]). Furthermore, it is difficult to model accurately all the complicated physical phenomena associated with electronic behavior.…”
Section: Introductionmentioning
confidence: 99%